Antimicrobial Activity of 4-Chlorocinnamic Acid Derivatives - Silva, Rayanne H. N. (Biomed Res Int, 2019)
The microbial resistance of fungi and bacteria is currently considered a major public health problem. Esters derived from cinnamic acid have a broad spectrum of pharmacological properties that include antimicrobial activity. In this study, a collection of structurally related 4-chlorocinnamic acid esters was prepared using Fischer esterification reactions, alkyl or aryl halide esterification, and Mitsunobu and Steglich reactions. All of the esters were submitted to antimicrobial tests against strains of the species Candida albicans, Candida glabrata, Candida krusei, Candida guilliermondii, Pseudomonas aeruginosa, and Staphylococcus aureus. The compounds also were subjected to molecular docking study with the enzyme 14α-demethylase. Twelve esters derived from 4-chlorocinnamic acid were obtained, with yields varying from 26.3% to 97.6%, three of which were unpublished. The ester methyl 4-chlorocinnamate (1) presented activity against S. aureus at the highest concentration tested. In the antifungal evaluation, all of the esters were bioactive, but methoxyethyl 4-chlorocinnamate (4) and perillyl 4-chlorocinnamate (11) were the most potent (MIC = 0.13 and 0.024 μmol/mL, respectively). The data of molecular docking suggested that all the compounds present good affinity towards the active site related to antifungal activity. Therefore, the esters tested may be inhibitors of the enzyme 14α-demethylase. In addition, the results demonstrate that substituents of short alkyl chains with presence of heteroatom, such as oxygen, or those with a perillyl type terpenic substructure promote better antifungal profiles.